1975
DOI: 10.1128/jvi.15.3.540-549.1975
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoproteins: structural components of oncornaviruses

Abstract: Oncornaviruses, which contain a virion-associated protein kinase, were found to possess phosphoproteins as virion structural components. One major phosphoprotein common to strains of laboratory and wild mouse oncornaviruses and a strain of feline leukemia virus was shown to be a polypeptide of about 12, 000 mol wt. In addition to this, the Kirsten strain of murine sarcoma virus contained a second major phosphoprotein of about 10, 000 mol wt, and mouse erythroblastosis virus contained a second major phosphoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1977
1977
1988
1988

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…However, the phosphorylated amino acids undergo complete hydrolysis to serine and threonine during the standard 24-h acid treatment used and thus cannot be detected upon subsequent amino acid analysis. To assay for the presence of phosphoserine or phosphothreonine, samples of p15 were subjected to a 5-h hydrolysis protocol which did not destroy phosphoamino acids (37), and the resulting hydrolysates were analyzed by standard procedures (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phosphorylated amino acids undergo complete hydrolysis to serine and threonine during the standard 24-h acid treatment used and thus cannot be detected upon subsequent amino acid analysis. To assay for the presence of phosphoserine or phosphothreonine, samples of p15 were subjected to a 5-h hydrolysis protocol which did not destroy phosphoamino acids (37), and the resulting hydrolysates were analyzed by standard procedures (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, our results indicated that EIAV p15 contains phosphoserine or phosphothreonine or both, although the relative abundance of each amino acid could not be determined by this method. However, attempts to incorporate 32p; into pl5 by standard in vivo procedures (18,37) have been unsuccessful, perhaps due to suboptimal labeling conditions for the equine kidney cells.…”
Section: Resultsmentioning
confidence: 99%
“…The ppl2 of 292 field isolate was also used to determine peptide homology between the nonphosphorylated and variously phosphorylated ppl2 species. The pp12 purified from 292 virus, labeled with 3H-amino acids and [32P]phosphate (13,14), was resolved by DEAE-cellulose chromatography (18) into three major peaks. One was non-phosphorylated, and the other two varied in the degree of phosphorylation (data not shown).…”
Section: ~~~~~~~~~-mentioning
confidence: 99%
“…Structural proteins of type C RNA tumor viruses consist of a major high-molecular-weight glycoprotein and several low-molecular-weight non-glycosylated proteins. One of the non-glycosylated proteins has been shown to be the major structural phosphoprotein of the virion (13,14). In viruses of lower mammalian species, including mice, rats, cats, minks, and pigs, the 12,000-dalton protein (p12) is always phosphorylated (ppl2) (13, 14; our unpublished data).…”
mentioning
confidence: 93%
“…Phosphorylated proteins similar to NS have been found in other RNA and DNA viruses (8,20,22) and are often associated with the viral nucleic acid (10,16). There is an indication that the degree of phosphorylation may play a regulatory role in viral replication.…”
mentioning
confidence: 99%